Science into Policy: Participatory Development of Biomass Energy Regulatory Instruments in Kenya - Njenga, M.; Mendum, R.; Gitau, J.K.; Wandera, F.O.; Herzog, S.; Ayalo, P.; Duguma, L.A.; Kipruto, W.; Ochieng, C.; Wanjohi, D.; Ngotho, M.; Despioch, B.; et al. (World Agroforestry Centre, 2021)
Biomass energy, mainly as solid biomass charcoal and firewood (woodfuel), plays a significant role as cooking energy in Kenya, as in many other countries in Africa. Despite its multiple benefits, unsustainable practices have negative environmental and health impacts. Efforts to transition from woodfuel to other forms of cooking energy have been in place for many years, but woodfuel still remains the key cooking fuel in Kenya due to its affordability and accessibility, cultural norms, as well as lack of access to affordable clean cooking alternatives.